KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MODEL PEMBELAJARAN INQUIRI TERBIMBING DAN MEANS ENDS ANALYSIS - Sari, Yenny Puspita; Masri, Masri (Jurnal Math-UMB.EDU, 2020)
In this research aims to see the difference of mathematical problem solving students with Guided Inquiry learning model and Means Ends Analysis (MEA) learning model. This research was a quasi-experimental research in SMPN 14 Kota Bengkulu. The population of this research is all of VIII class students, with the sample of research is VIII I class as the experimental class I that given using guided inquiry model treatment, students of class VIII 3 as the experimental class II that given Means Ends Analysis model treatment, students of class VIII 2 as the control class that given conventional model treatment. The data collection of students result study using mathematical problem solving skills test consists of pre-test and post-test. The data obtained were analyzed using one path ANAVA and continued with BNT test. Based on the ANAVA result there is a difference between students' mathematical problem solving abilities in experimental class I, experimental class II and control class. From the BNT test that the treatment between experimental class I given the Guided Inquiry, Experimental class II treatment given the Means Ends Analysis Â treatment no difference in mathematical problem solving ability, while experimental class I (Guided Inquiry) with control and experimental class II Means Ends Analysis with the control there is a difference in problem solving abilities mathematically and the highest average score was obtained in the students treated with the Guided Inquiry model.Â  Keywords : Ability of Mathematical Problem Solving Students, Guided Inquiry Model, Means Ends Analysis Model